2022
DOI: 10.1186/s12978-022-01459-x
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of infertility among couples who desire a first and second child in Shanghai, China: a facility-based prospective cohort study

Abstract: Background With the implementation of the two-child policy in China, more couples have expressed the desire to have another child. We conducted this study to evaluate the incidence of infertility and risk factors in couples intending to have a first and second child. Methods From 2013 to 2017, a prospective cohort study was conducted at the pre-pregnancy center of the International Peace Maternal and Child Health Hospital. The participants were sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The age of infertile woman (>35 years) was another independent risk factor for depressive symptoms (P<0.05). These finding was similar to many previous study conducted in other provinces of China [ 13 , 14 ]. And the possible reason might be that with the increase of age, the probability of successful conception of infertile patients will gradually decrease [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The age of infertile woman (>35 years) was another independent risk factor for depressive symptoms (P<0.05). These finding was similar to many previous study conducted in other provinces of China [ 13 , 14 ]. And the possible reason might be that with the increase of age, the probability of successful conception of infertile patients will gradually decrease [ 33 ].…”
Section: Discussionsupporting
confidence: 93%
“…In Japan, about 67% of unmarried women believe that couples should have at least one child after marriage, while about 25% of married women believe that a couple is socially acceptable only after they have children, according to the study [ 12 ]. In China, people attach great importance to fertility [ 13 , 14 ]. Even though women have relatively high family decision-making power than in the past, there still exist a tendency in society to think that "it is always women’s fault to have no children” [ 5 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we experienced a loss to follow-up for 15 992 women who lacked birth records. Possible reasons for these missing records include infertility (16.95%, n = 2177 in Shanghai) as reported by Zhu et al (2022), and pregnancy loss (ranging between 10% and 24%) as indicated by Jiang et al (2023). The impact of this loss to follow-up on greenness effects remains uncertain.…”
Section: Discussionmentioning
confidence: 99%
“…For decades, the percentage of childlessness among women remained low, with a rate of 1.46% for women aged 40–49 in the 1982 population census,10 1.69% for women aged 49 in the 1987 1% population sample survey,11 1.25% for women aged 49 in the 1990 population census,12 less than 2% for women aged 49 in the 2017 National Fertility Survey13 and 4.16% for women aged 49 in the 2015 1% population sample survey 14. However, over the past few decades, there has been a gradual increase in the prevalence of childlessness, specifically as a result of infertility 15–18. The National Health Commission of China indicated that the incidence of infertility was between 7% and 10% in 2021 19.…”
Section: Introductionmentioning
confidence: 99%